Current status of solar PV and the possibility of agrivoltaic in dry areas - IIDA, Tetsunari (Journal of Arid Land Studies, 2020)
In 2020, the increase in the number of infected people due to the new coronavirus infection (COVID-19) pandemic and the stagnation of economic and social activities due to lockdown, etc. The economy as a whole, including industry and finance, is expected to stagnate and cool more than the Lehman shock in 2008. In addition to the recovery from ongoing economic crisis, the voices calling for green recovery to tackle the long-standing climate crisis and the social disparity highlighted by COVID-19 are resonating anywhere in the world including Japan. Renewable energy, especially agrivoltaic, which is the subject of this paper, is expected to be the center of such measures.